A Brandy Aroma Wheel for South African Brandy - Jolly, N.P.; Hattingh, S. (South African Journal of Enology and Viticulture, 2017)
A Brandy Aroma Wheel was developed incorporating standardised descriptive terminology (descriptors) for South African brandy aroma. The wheel comprises two tiers of descriptors with 18 first-tier descriptors giving a broader definition of an aroma, while the 75 second-tier descriptors give a more precise definition. Reference standards have been developed for the second-tier descriptors. Brandy aroma scorecards have also been developed for use with the Brandy Aroma Wheel.